Reduction in nitrogen fertilizer applications by the use of polymer‐coated urea: effect on maize yields and environmental impacts of nitrogen losses. (8th January 2019) - Xie, Yong; Tang, Li; Han, Yongliang; Yang, Lan; Xie, Guixian; Peng, Jianwei; Tian, Chang; Zhou, Xuan; Liu, Qiang; Rong, Xiangmin; Zhang, Yuping
Abstract: BACKGROUND: Urea is commonly over‐applied as a nitrogen (N) fertilizer to crops in southern China and has a low utilization efficiency as a result of the high precipitation and high temperatures in this region. This has led to a need to optimize the management of N fertilizer use in maize crops on the subtropical hilly uplands of southern China. RESULTS: We investigated the effects of applying different amounts of N in the form of polymer‐coated urea (PCU) on the yield of maize and gaseous losses of N from soils in the form of NH3 and N2 O. The field plots used in this trial had zero‐added N (0 kg N ha −1 ), the addition of urea (240 kg N ha −1 ) and four levels of fertilization with PCU (1 PCU, 0.9 PCU, 0.8 PCU and 0.7 PCU), which represented a 0%, 10%, 20% and 30% reduction, respectively, in the application of PCU‐N relative to the urea plot. Compared to the urea plot, there was little variation in the yield of maize for all the PCU‐N treatments, with a significant improvement in the utilization efficiency of N (up to 46.0–51.2%) with a 0–30% reduction in the application of PCU‐N. Significant effects in the mitigation of the N2 O emission flux and the accumulation of N2 O‐N were observed in the 0.8 PCU and 0.7 PCU plots. The application of PCU‐N significantly reduced the flux and total amount of NH3 ‐N lost to the environment: as the application rate for N decreased by 0–30%, the NH3 loss was significantly reduced by 12.7–36.1%. CONCLUSION: The findings of the present study suggest that the use of PCU could allow a reduction in the application of N of 20–30% compared to traditional agricultural practices in this area with the same yield of maize, although with significantly decreased NH3 and N2 O losses and the increased utilization of N. © 2018 Society of Chemical Industry